PENGEMBANGAN MEDIA PEMBELAJARAN VIDEO ANIMASI BERBANTUAN PLATFORM DORATOON PADA MATERI BUDAYA DAERAHKU - Amalia Mustika Zahra; Yuli Mulyawati; Aip M. Irpan (STKIP Subang, 2025)
This research aims to develop and test the feasibility and effectiveness of animationvideo learning media assisted by the Doratoon platform on the Budaya Daerahkumaterial. This research is research and development with the ADDIE model whichincludes analysis, design, development, implementation, and evaluation. Initialobservations show that learning at SDN Cilember 01 is still dominated by lecturemethods with book media, making it less attractive for students. The developedmedia was validated by experts with a feasibility percentage of 98.3% (mediaexperts), 94% (linguists), 92% (subject matter expert 1), and 96% (subject matterexpert 2) indicating that the media is very feasible to use. The trial on 35 studentsin grade V resulted in a positive response from students (87%) and teachers (90%),as well as an increase in average scores from 60 to 83.7. This media is consideredfeasible and effective to improve student learning outcomes, understanding, andmotivation.